Pelecehan Seksual dalam Dunia Maya : Studi Kasus Terhadap Penggunaan Media Sosial - Dewi Utama, Cika Suci; Majid, Nur Kholis (Indonesian Journal Publisher, 2024)
The objective of this research is to identify the factors causing sexual harassment on social media and its impact on gender, as well as to analyze the number of sexual harassment cases that occurred in 2020. The methodology employed in this study involves data analysis from partner institutions of the National Commission on Violence Against Women (Komnas Perempuan) and the Service and Referral Unit (UPR) of Komnas Perempuan. The data encompasses the quantity of sexual harassment cases on social media and cases of violence against women in general. The research findings indicate a significant decrease in the number of sexual harassment cases on social media in 2020, with only 120 institutions returning questionnaires, down from 239 institutions the previous year. However, there is an increase in overall cases of violence against women, with 8,234 cases handled by the partner institutions of Komnas Perempuan. From this study, it can be concluded that despite the decline in the number of sexual harassment cases on social media, cases of violence against women in general continue to rise. This suggests that sexual harassment on social media and violence against women are issues that need continuous identification and serious attention.